Effect of pre - and post-harvest treatments on yield and fruit quality of selected banana cultivars - Elkashif, Mohamed; Mohamed, Hagir; Elamin, Osman (Gezira Journal of Agricultural Science, 2010)
This study was conducted at the experimental farm of the National Institute for the Promotion of Horticultural Exports during 2005/06 to investigate the effect of different materials used for pre-harvest bagging of banana bunches on fruit quality and yield of selected cultivars. Bagging materials used were cotton cloth, jute and transparent polyethylene film. The cultivars were Grandnain (GN), William's Hybrid (WH) and the locally grown Dwarf Cavendish (DC). Treatments were arranged in a split-plot design with three replications. The cultivars were the main plots and the bagging materials were the sub-plots. Also, the effects of post-harvest packaging treatments on fruit quality were studied. Packaging treatments were cartons lined with polyethylene film, cartons without polyethylene and the unpackaged control. Jute and cotton cloth bagging materials significantly reduced the incidences of sunscald and physical injury in banana bunches as compared to polyethylene and the unbagged control. Also, the highest bunch and hand weights were obtained when cloth and jute materials were used as compared to the other treatments. The cloth bagging material resulted in the longest green life and the unbagged control resulted in the shortest. The cultivar WH resulted in the longest green life and the highest yield components, followed by GN and the lowest values were recorded for DC. In all cultivars, post-harvest packaging of banana fruit in cartons lined with polyethylene film resulted in the longest green life, the highest TSS content and the best taste, followed by those packed in cartons only and the worst results were obtained by the unbagged control. The cultivars WH and GN were superior in all fruit quality parameters as compared to the locally grown DC cultivar.    أجريت هذه الدراسة بالمزرعة التجريبية للمعهد القومي لتنمية الصادرات البستانية في الموسم 2005/06 لدراسة تأثير مواد تغطية سبائط الموز قبل الحصاد على جودة الثمار والإنتاج لبعض الأصناف المنتخبة. مواد التغطية المستخدمة كانت قماش قطني ( دمورية) وخيش وكيس نايلون شفاف. الأصناف كانت قران  نين (GN)، وليامز هايبرد (WH) والكافندش القزم (DC). استخدم تصميم القطع المنشقة بثلاث مكررات. كانت  الأصناف هي القطع الرئيسة ومواد التغطية القطع الثانوية. كذلك شملت الدراسة تأثير معاملات التغليف بعد الحصاد على جودة الثمار. معاملات التغليف كانت كراتين مبطنة بأكياس النايلون، كراتين بدون نايلون وأخرى بدون كراتين. مواد التغطية من الدمورية والخيش أعطت انخفاضاُ معنوياً في لفحة الشمس والإصابة الفيزيائية لسبائط الموز مقارنة بكيس النايلون الشفاف والسبائط المكشوفة. كذلك أعطت مواد التغطية المذكورة أعلى معدل لوزن السبائط والكفوف بالمقارنة مع المعاملات الأخرى. أعطت الدمورية أطول فترة صلاحية للثمار كما أعطت السبائط المكشوفة أقل فترة. أعطى الصنف WH أطول فترة صلاحية للثمار وأعلى إنتاجية، يليه GN وأقل معدلات كانت للصنف DC. تغليف الثمار في الكراتين المبطنة بأكياس النايلون أعطي أطول صلاحية للثمار وأعلى معدل للمواد الصلبة الذائبة وأفضل مذاق تليه الثمار المغلفة بكراتين فقط وأقل المعدلات كانت للثمار غير المغلفة. الأصناف WH و GN أعطت أفضل خصائص الجودة للثمار بالمقارنة مع الصنف المحلي DC.